Life-threatening nasotracheal tube obstruction by a blood clot: a case report - Dajeong Lee; Chan Yong Park; Sang Wha Kim (Journal of Trauma and Injury)
The nasotracheal tube (NTT) is frequently used in oral and maxillofacial surgery and is generally considered a safe means of protecting the airway while ensuring an adequate surgical field. The most common complication associated with NTT is epistaxis, and only a few cases of foreign body obstruction have been reported. In this case report, the authors aimed to highlight the potential for NTT obstruction following surgery. A 24-year-old female patient, who underwent mandibuloplasty and rhinoplasty at a local clinic, was referred to our hospital patient due to dyspnea and edema on her right mandibular angle. Even with NTT, patient continued to experience mild dyspnea and tachypnea, so a T-piece was applied. However, tachycardia accompanied by a sudden worsening of dyspnea was observed, and bag-valve-mask ventilation was initiated promptly. But oxygen saturation remained unimproved, so an emergency cricothyroidotomy was performed. After 4 hours, the patient’s condition stabilized. Upon examination, the previously inserted NTT was identified, and a blood clot approximately 10 cm long at the NTT tip was discovered, causing lumen obstruction. The obstructions of NTT can lead to serious or life-threatening consequences if left unobserved or ignored. Therefore, when a patient with an NTT complains of dyspnea, clinicians should promptly investigate the possibility of partial NTT obstruction to ensure the airway’s security.